Carbon dioxide absorbing fiber and its manufacturing method
Patent Information
- Application Number
- JP2022511964
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-22
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-03-22
AI Technical Summary
【0009】 本発明の二酸化炭素吸収繊維は、二酸化炭素吸収性に優れている。そのため、住環境下に存在する二酸化炭素を有効に除去することができる。
Smart Images

Figure 0007600213000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon dioxide absorbing fiber containing polyvinyl alcohol and an amine polymer, a method for producing the same, and a fiber assembly containing the carbon dioxide absorbing fiber. [Background technology]
[0002] In recent years, interest in carbon dioxide concentrations in living environments has been growing. It has been reported that an increase in carbon dioxide concentrations in living environments can lead to a decline in cognitive ability and discomfort, and it has become clear that controlling carbon dioxide concentrations is necessary to create a comfortable and productive environment. One of the materials that can remove carbon dioxide from the air is the use of inorganic porous materials. However, inorganic porous materials, such as zeolite, adsorb not only carbon dioxide but also other substances into their pores, so in the presence of water vapor, such as in living environments, their adsorption ability is significantly impaired, and gas drying equipment is required, making their application impractical.
[0003] An example of a material capable of absorbing carbon dioxide even in the presence of water is a carbon dioxide absorbent containing an amine-based polymer and an alcohol compound (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 059368 Summary of the Invention [Problem to be solved by the invention]
[0005] However, according to the investigations of the present inventors, it has been found that carbon dioxide absorbents such as those described in Patent Document 1, particularly when processed into fibers, are unable to sufficiently absorb carbon dioxide present in living environments because gas diffusion within the material is extremely slow due to the gas barrier properties of the alcohol compound, etc.
[0006] Therefore, an object of the present invention is to provide a carbon dioxide absorbing fiber having excellent carbon dioxide absorbency, a method for producing the same, and a fiber assembly containing the carbon dioxide absorbing fiber. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the present inventors have found that the above problems can be solved by adjusting the nitrogen element concentration on the surface of a carbon dioxide absorbing fiber containing polyvinyl alcohol and an amine polymer to 1.40 times or more the nitrogen element concentration in the entire fiber, and have completed the present invention. That is, the present invention includes the following aspects.
[0008] [1] A carbon dioxide absorbing fiber containing polyvinyl alcohol and an amine polymer, wherein the nitrogen element concentration on the fiber surface is 1.40 times or more higher than the nitrogen element concentration in the entire fiber. [2] The carbon dioxide absorbing fiber described in [1], wherein the nitrogen element concentration on the fiber surface is 50 mol % or more. [3] The carbon dioxide absorbing fiber according to [1] or [2], wherein the content of the amine polymer is 5 to 50 mass % based on the mass of the carbon dioxide absorbing fiber. [4] The carbon dioxide absorbing fiber according to any one of [1] to [3], wherein the amine-based polymer is at least one selected from the group consisting of polyvinylamine, polyallylamine, polydiallylamine, polyalkyleneamine, polyethyleneimine, polydiallyl quaternary ammonium, and salts thereof. [5] The carbon dioxide absorbing fiber according to any one of [1] to [3], wherein the amine-based polymer is an amine-based polymer having a branched structure. [6] The carbon dioxide absorbing fiber according to any one of [1] to [5], wherein the number average molecular weight of the amine-based polymer is 500 to 50,000. [7] A method for producing a carbon dioxide absorbing fiber according to any one of [1] to [6], comprising: a step (1) of obtaining a spinning dope containing polyvinyl alcohol, an amine-based polymer and a solvent; a step (2) of extruding the spinning dope into dry air and removing the solvent to form an undrawn fiber; and a step (3) of drawing the undrawn fiber to 2.5 times or more. [8] The method according to [7], wherein the stretching temperature in step (3) is 150 to 250°C. [9] A fiber assembly comprising the carbon dioxide absorbing fiber according to any one of [1] to [6].
[10] The fiber assembly according to [9], which is a nonwoven fabric. Effect of the Invention
[0009] The carbon dioxide absorbing fiber of the present invention has excellent carbon dioxide absorbing properties, and therefore can effectively remove carbon dioxide present in the living environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Carbon dioxide absorbing fiber] The carbon dioxide absorbing fiber of the present invention contains polyvinyl alcohol and an amine-based polymer. In this specification, carbon dioxide absorbency refers to the property of being able to absorb carbon dioxide.
[0011] <Polyvinyl alcohol> The polyvinyl alcohol (sometimes referred to as PVA) contained in the carbon dioxide absorbing fiber of the present invention is a polymer having mainly structural units derived from vinyl alcohol and structural units derived from vinyl ester (preferably vinyl acetate). The polyvinyl alcohol may contain structural units derived from monomers (sometimes referred to as other monomers) other than these structural units within a range that does not impair the effects of the present invention.Examples of other monomers include α-olefins such as ethylene, propylene, n-butene, and isobutylene; acrylic acid and its salts, acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid and its salts; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, methacrylic acid, and methacrylic acid. methacrylic acid esters such as i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or its quaternary salts, N-methylolacrylamide, and and its derivatives; methacrylamide derivatives such as methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, methacrylamide propanesulfonic acid and its salts, methacrylamide propyl dimethylamine and its salts or its quaternary salts, N-methylol methacrylamide and its derivatives; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts or esters; vinyl silyl compounds such as vinyl trimethoxysilane; and isopropenyl acetate. These other monomers can be used alone or in combination of two or more.From the viewpoint of easily increasing the carbon dioxide absorbency, the content of the constituent units derived from other monomers is usually 20 mol% or less, preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 1 mol% or less, based on the total molar amount of the constituent units constituting the polyvinyl alcohol. The polyvinyl alcohol can be used alone or in combination of two or more kinds.
[0012] Polyvinyl alcohol may be produced by a known method, for example, a method of saponifying a resin obtained by polymerizing a vinyl ester (preferably vinyl acetate) and, if necessary, the other monomers in a state of being dissolved in a solvent such as alcohol. Examples of the solvent used in this method include lower alcohols such as methanol and ethanol. The alcohol used in the saponification reaction may contain a solvent such as acetone, methyl acetate, ethyl acetate, or benzene, so long as the amount of the alcohol is 40% by mass or less. Examples of the catalyst used in the saponification reaction include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, alkali catalysts such as sodium methoxide, and acid catalysts such as mineral acids. There is no particular restriction on the temperature of the saponification reaction, but a range of, for example, 20 to 60°C is preferable. The vinyl alcohol obtained by the saponification reaction is preferably washed and then dried.
[0013] The saponification degree of polyvinyl alcohol is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, particularly preferably 95 mol% or more, and preferably 100 mol% or less, more preferably 99.5 mol% or less. If the saponification degree is equal to or more than the lower limit, the stability of the spinning solution is easily improved, and if the saponification degree is equal to or less than the upper limit, the carbon dioxide absorbency is easily improved. The saponification degree of polyvinyl alcohol can be measured according to JIS-K6726.
[0014] The viscosity average degree of polymerization of polyvinyl alcohol is preferably 200 or more, more preferably 500 or more, even more preferably 700 or more, particularly preferably 1000 or more, and preferably 5000 or less, more preferably 4000 or less, even more preferably 3000 or less, particularly preferably 2500 or less. When the viscosity average degree of polymerization of polyvinyl alcohol is above the above lower limit, the spinnability is easily improved. When the viscosity average degree of polymerization is below the above upper limit, the pressure loss is suppressed and the productivity is easily improved. In addition, since it is easy to suppress the aggregation of fibers, it is advantageous in terms of strength and the moldability is also easily improved. The viscosity average degree of polymerization of polyvinyl alcohol can be measured, for example, based on JIS-K6726 "Polyvinyl Alcohol Test Method", for example, by the method described in the Examples.
[0015] The content of polyvinyl alcohol contained in the carbon dioxide absorbing fiber is preferably 95% by mass or less, more preferably 85% by mass or less, even more preferably 75% by mass or less, even more preferably 70% by mass or less, particularly preferably 65% by mass or less, and preferably 50% by mass or more, based on the mass of the carbon dioxide absorbing fiber. If the content of polyvinyl alcohol is below the above upper limit, the gas barrier property is reduced, making it easier to increase the carbon dioxide absorbency, and if the content of polyvinyl alcohol is above the above lower limit, it is advantageous in terms of strength and moldability.
[0016] <Amine-based polymer> The amine-based polymer contained in the carbon dioxide absorbing fiber is a polymer capable of adsorbing carbon dioxide (CO2) by amino groups and quaternary ammonium groups. The amino groups of the amine-based polymer may be any of primary amino groups, secondary amino groups, and tertiary amino groups. The repeating units (sometimes called constituent units) having amino groups may be one type or two or more types. Therefore, the amine-based polymer may be a polymer in which two or more types of repeating units having amino groups or quaternary ammonium groups are randomly, block, alternately, or graft-copolymerized. Furthermore, the amine-based polymer may have repeating units that do not have amino groups or quaternary ammonium groups within a range that does not impair the effects of the present invention.
[0017] Examples of amine-based polymers include polyvinylamine, polyvinyl alkylamine, polyalkyleneamine, polyethyleneimine, quaternary ammonium-containing polymer, polyaniline, polynucleotide, polyallylamine, polydiallylamine, polyalkyleneamine, polydiallyl quaternary ammonium, and salts thereof. The amine-based polymers can be used alone or in combination of two or more. Copolymers in which two or more repeating units of these polymers are copolymerized can also be used. Among these, from the viewpoint of easily increasing carbon dioxide absorption, at least one selected from the group consisting of polyvinylamine, polyallylamine, polydiallylamine, polyalkyleneamine, polyethyleneimine, polydiallyl quaternary ammonium, and salts thereof is preferred, at least one selected from the group consisting of polyallylamine, polydiallylamine, polydiallyl quaternary ammonium, polyethyleneimine, and salts thereof is more preferred, and polyethyleneimine and / or its salts are even more preferred.
[0018] In one embodiment of the present invention, the amine-based polymer is preferably an amine-based polymer having a branched structure. When such an amine-based polymer having a branched structure is used, the amine-based polymer is likely to be unevenly distributed on the fiber surface, so that the nitrogen element concentration on the fiber surface is likely to be increased, and the carbon dioxide absorption is likely to be improved. For example, polyethyleneimine includes those having a linear structure containing primary amines and secondary amines, and those having a branched structure containing at least tertiary amines, but from the viewpoint of easily increasing the carbon dioxide absorption, polyethyleneimine having a branched structure is preferred.
[0019] The number average molecular weight of the amine polymer is preferably 500 or more, more preferably 1,000 or more, even more preferably 3,000 or more, even more preferably 5,000 or more, particularly preferably 8,000 or more, and is preferably 50,000 or less, more preferably 30,000 or less, even more preferably 20,000 or less, particularly preferably 15,000 or less. When the number average molecular weight of the amine polymer is equal to or more than the above lower limit, the adhesion with polyvinyl alcohol is improved, and it is easy to prevent the bleed-out of the amine polymer. When the number average molecular weight is equal to or less than the above upper limit, it is easy to improve the compatibility with polyvinyl alcohol, and it is easy to improve the spinnability. In addition, it is easy to increase the nitrogen element concentration on the fiber surface, and it is easy to improve the carbon dioxide absorbency. The number average molecular weight of the amine polymer can be obtained by dissolving the amine polymer in a solvent capable of dissolving it and using gel permeation chromatography (GPC), and can be measured, for example, by the method described in the Examples.
[0020] The content of the amine-based polymer contained in the carbon dioxide absorbing fiber of the present invention is preferably 5% by mass or more, more preferably 15% by mass or more, even more preferably 25% by mass or more, even more preferably 30% by mass or more, particularly preferably 35% by mass or more, particularly preferably 40% by mass or more, and preferably 50% by mass or less, based on the mass of the carbon dioxide absorbing fiber. When the content of the amine-based polymer is equal to or more than the above lower limit, the carbon dioxide absorbency is easily improved. When the content of the amine-based polymer is equal to or less than the above upper limit, it is advantageous in terms of strength and moldability.
[0021] <Carbon dioxide absorbing fiber> The carbon dioxide absorbing fiber of the present invention contains the polyvinyl alcohol and the amine-based polymer, and the nitrogen element concentration on the fiber surface is 1.40 times or more the nitrogen element concentration of the entire fiber, so that it can have excellent carbon dioxide absorption. In the adsorption fiber containing polyvinyl alcohol, the amine-based polymer inside the surface cannot partially contribute to the adsorption of carbon dioxide due to the influence of the gas barrier property of the polyvinyl alcohol present on the fiber surface, but in the present invention, such an amine-based polymer is unevenly distributed on the fiber surface (or is present in large amounts on the fiber surface), so it is presumed that the carbon dioxide absorption is improved. Therefore, the carbon dioxide absorbing fiber of the present invention can be suitably used as a fiber-shaped adsorbent and can control the carbon dioxide concentration in a living environment. Moreover, since it can absorb even a small amount of carbon dioxide in a living environment, it is possible to avoid adverse effects such as a decrease in cognitive ability and discomfort on humans.
[0022] The nitrogen element concentration on the fiber surface is preferably 1.70 times or more, more preferably 1.90 times or more, even more preferably 2.00 times or more, and particularly preferably 2.10 times or more, relative to the nitrogen element concentration in the entire fiber. When the nitrogen element concentration on the fiber surface relative to the nitrogen element concentration in the entire fiber (sometimes referred to as the nitrogen concentration ratio (surface / whole)) is equal to or more than the lower limit, the amine polymer is more unevenly distributed on the fiber surface, and therefore the carbon dioxide absorbency is more likely to be improved. In addition, the upper limit of the nitrogen concentration ratio (surface / whole) is preferably 20 times or less, more preferably 10 times or less, and even more preferably 5 times or less.
[0023] In this specification, the nitrogen element concentration means the ratio of the amount of nitrogen element to the total amount of nitrogen element and oxygen element, and can be calculated by the following formula (1). Nitrogen concentration (mol%) = nitrogen amount (mol) / [nitrogen amount (mol) + oxygen amount (mol)] × 100 (1)
[0024] The nitrogen element concentration on the fiber surface can be calculated by measuring the amount of oxygen element (mol) and the amount of nitrogen element (mol) using XPS (X-ray photoelectron spectroscopy) and calculating it by formula (1). More specifically, the nitrogen element concentration on the fiber surface can be measured using a photoelectron spectrometer under the measurement conditions of excitation source: MgKα, analysis size: 1 mm, and incidence angle: 45°, for example, by the method described in the Examples. In a preferred embodiment of the present invention, the spectrum peak of the oxygen element and the spectrum peak of the nitrogen element may appear near 530 eV and near 398 eV, respectively. In addition, when the carbon dioxide absorbing fiber contains additives and the like described below, the additives may be removed using a solvent in which amine-based polymers and polyvinyl alcohol are not dissolved before the measurement, and then the XPS measurement and the elemental analysis described below may be performed. For example, in an embodiment in which an oil agent or the like is attached to the fiber surface, the fiber may be washed with an organic solvent such as hexane in which amine-based polymers and polyvinyl alcohol are not dissolved and oil agents and the like can be dissolved before the element amount measurement, and then the measurement may be performed.
[0025] The nitrogen element concentration in the entire fiber can be calculated by the amount of oxygen element (mol) and the amount of nitrogen element (mol) using an elemental analysis method, and can be obtained by formula (1). More specifically, the nitrogen element concentration in the entire fiber can be measured using an organic elemental analyzer under the following measurement conditions: analysis conditions: CNHS, incinerator temperature: 950°C, oven temperature: 65°C, helium: 140mL / min, oxygen: 250mL, standard sample: sulfanilamide, for example, by the method described in the Examples. The nitrogen element concentration on the fiber surface and the nitrogen element concentration throughout the fiber may be calculated from the element ratio (molar ratio) of the amount of oxygen element to the amount of nitrogen element according to formula (1).
[0026] The nitrogen element concentration on the fiber surface is preferably 50 mol% or more, more preferably 60 mol% or more, even more preferably 65 mol% or more, even more preferably 70 mol% or more, particularly preferably 75 mol% or more, and particularly preferably 80 mol% or more. When the nitrogen element concentration on the fiber surface is equal to or higher than the above lower limit, the carbon dioxide absorbency is easily increased. Moreover, the upper limit of the nitrogen element concentration on the fiber surface is preferably 95 mol% or less, more preferably 90 mol% or less. When the nitrogen element concentration on the fiber surface is equal to or lower than the above upper limit, the tackiness of the fiber surface is suppressed, and the handleability is easily improved. Thus, in a preferred embodiment of the present invention, the nitrogen element concentration on the fiber surface is 95 mol% or less, and the fiber is not a fiber formed by applying an amine-based polymer to the surface of polyvinyl alcohol, but a fiber in which polyvinyl alcohol and an amine-based polymer are composited.
[0027] The nitrogen element concentration in the entire fiber is preferably 5 mol% or more, more preferably 10 mol% or more, and is preferably 50 mol% or less, more preferably 45 mol% or less, and even more preferably 40 mol% or less. When the nitrogen element concentration in the entire fiber is within the above range, the carbon dioxide absorbency is easily improved. The method for adjusting the nitrogen concentration ratio (surface / whole) and the nitrogen element concentration to the above range is not particularly limited, and examples thereof include the use of the manufacturing method described below (particularly the manufacturing method including step (3)) and the use of the above polyvinyl alcohol or amine-based polymer (particularly the preferred one described above).
[0028] In one embodiment of the present invention, the single fiber fineness of the carbon dioxide absorbing fiber of the present invention is not particularly limited, but is preferably 0.1 dtex or more, more preferably 1 dtex or more, even more preferably 5 dtex or more, particularly preferably 8 dtex or more, and is preferably 100 dtex or less, more preferably 70 dtex or less, and even more preferably 45 dtex or less. When the single fiber fineness is within the above range, the carbon dioxide absorbency is easily improved. The single fiber fineness can be measured, for example, by the method described in the Examples.
[0029] In one embodiment of the present invention, the saturated carbon dioxide absorption of the carbon dioxide absorbing fiber of the present invention is preferably 42 mg / g or more, more preferably 45 mg / g or more, even more preferably 60 mg / g or more, even more preferably 80 mg / g or more, particularly preferably 100 mg / g or more, and particularly preferably 110 mg / g or more. When the saturated carbon dioxide absorption is above the above lower limit, excellent carbon dioxide absorption can be exhibited. The saturated carbon dioxide absorption means the amount of carbon dioxide absorbed by the carbon dioxide absorbing fiber after leaving the carbon dioxide absorbing fiber for one week (168 hours) under an environment of 20°C temperature, 60% relative humidity, and 400 ppm carbon dioxide concentration, and can be measured, for example, by the method described in the Examples.
[0030] In one embodiment of the present invention, the carbon dioxide absorption amount that the carbon dioxide absorbing fiber of the present invention can absorb in 12 hours is preferably 20 mg / g or more, more preferably 25 mg / g or more, and even more preferably 30 mg / g or more. When the carbon dioxide absorption amount that can be absorbed in 12 hours is equal to or more than the above lower limit, excellent carbon dioxide absorption properties can be exhibited. The carbon dioxide absorption amount that can be absorbed in 12 hours is the saturated carbon dioxide absorption amount described above, but the time for which the carbon dioxide absorbing fiber is left standing is changed to 12 hours, and can be measured, for example, by the method described in the Examples.
[0031] The carbon dioxide absorbing fiber of the present invention may contain any additive other than the polyvinyl alcohol and the amine-based polymer. Examples of the additive include polymers other than polyvinyl alcohol and amine-based polymers; antioxidants; stabilizers; lubricants; processing aids; antistatic agents; colorants; impact resistance aids; foaming agents; crosslinking agents, etc. The additives may be used alone or in combination of two or more. The content of the additive may be preferably 10% by mass or less, more preferably 5% by mass or less, based on the mass of the carbon dioxide absorbing fiber.
[0032] In one embodiment of the present invention, the carbon dioxide absorbing fiber of the present invention preferably has a dynamic friction coefficient of 1.0 or less, more preferably 0.8 or less, even more preferably 0.6 or less, and particularly preferably 0.4 or less. When the dynamic friction coefficient is equal to or less than the above upper limit, the carbon dioxide absorbing fiber has excellent fiber processability (woven / knitted / nonwoven fabric) and handleability, and is easily developed into various forms of fiber products. There is no particular limit to the lower limit, but it is usually 0 or more. The dynamic friction coefficient can be measured by the method described in the examples below. The dynamic friction coefficient can be adjusted by appropriately selecting the type or content of polyvinyl alcohol or amine-based polymer contained in the carbon dioxide absorbing fiber, the manufacturing method of the carbon dioxide absorbing fiber, etc., and may be adjusted to the above range, for example, by using the above-mentioned preferred type and content of polyvinyl alcohol or amine-based polymer, the below-mentioned preferred manufacturing method of the carbon dioxide absorbing fiber, etc.
[0033] [Method of manufacturing carbon dioxide absorbing fiber] As a method for producing the carbon dioxide absorbing fiber of the present invention, for example, a method including a step (1) of obtaining a spinning dope containing the polyvinyl alcohol, the amine-based polymer, and a solvent, a step (2) of extruding the spinning dope into dry air and removing the solvent to form an undrawn fiber, and a step (3) of drawing the undrawn fiber to 2.5 times or more can be suitably used.
[0034] In step (1), the polyvinyl alcohol, the amine-based polymer, the solvent, and optionally the additives are mixed to obtain a spinning dope. Examples of the solvent include water, dimethyl sulfoxide (DMSO), glycerin, ethylene glycol, and a mixed solvent thereof. From the viewpoint of the solubility of the polymer and the ease of removing the solvent, it is preferable to use water. In a preferred embodiment, it is preferable to obtain a spinning dope by dissolving the polyvinyl alcohol, the amine-based polymer, the solvent, and optionally the additives using a batch-type dissolution tank and an extruder. The extruder may be a single-screw extruder or a twin-screw extruder, and a twin-screw extruder can be preferably used from the viewpoint of mixability. The order of introduction into the extruder is not particularly limited, but from the viewpoint of mixability, it is preferable to introduce the mixed solution of polyvinyl alcohol and the solvent into the extruder and knead it, and then further introduce the amine-based polymer and optionally the additives into the extruder and knead it. The temperature during mixing and the screw rotation speed of the extruder may be appropriately adjusted so that the polymer can be dissolved in the solvent. The temperature during mixing may be, for example, 80 to 160°C, and preferably 110 to 150°C.
[0035] Step (2) is a step of forming an undrawn fiber from the spinning dope obtained in step (1) by a dry spinning method. The carbon dioxide absorbing fiber of the present invention can be produced by a wet spinning method, a dry-wet spinning method, or a dry spinning method. However, when the fiber is produced by a wet spinning method or a dry-wet spinning method, it is difficult to obtain a carbon dioxide absorbing fiber having a relatively high content of the amine polymer, since the amine polymer may be dissolved in the solidification bath. Therefore, in the production method of the present invention, it is preferable to produce the fiber by a dry spinning method in which such a problem does not occur, as in step (2).
[0036] The dry spinning method in step (2) includes a method in which the spinning dope is extruded through a nozzle into heated dry air, and the solvent is evaporated and removed to form fibers. The dried fibers may be wound up using a winding device or the like. As described above, the dry spinning method does not require the use of a solidification bath, and therefore, compared with the wet spinning method or the dry-wet spinning method, a carbon dioxide absorbing fiber having a high content of amine-based polymer can be obtained simply and efficiently. The number of holes in the nozzle is not particularly limited, and is, for example, 10 to 1000. The temperature of the dry air may be any temperature that can remove the solvent, and is preferably 50 to 200°C, more preferably 60 to 150°C.
[0037] Step (3) is a step of stretching the unstretched fiber obtained in step (2) to 2.5 times or more. The present inventor unexpectedly found that by subjecting the unstretched fiber to a predetermined stretching treatment at a stretching ratio of 2.5 times or more, the amine-based polymer in the carbon dioxide absorbing fiber can be unevenly distributed on the fiber surface, and the nitrogen concentration ratio (surface / whole) can be adjusted to 1.40 times or more. This is presumably because, in a fibrous form, the amine-based polymer is energetically more stable when present on the surface than when present inside. The stretching ratio is preferably 2.8 times or more, more preferably 3.0 times or more, even more preferably 3.5 times or more, even more preferably 4.0 times or more, particularly preferably 4.5 times or more, and particularly preferably 5.0 times or more. When the stretching ratio is equal to or more than the above lower limit, the amine-based polymer is more likely to be unevenly distributed on the fiber surface, and therefore the nitrogen concentration ratio (surface / whole) and the nitrogen element concentration on the fiber surface are easily increased.
[0038] In step (3), the stretching temperature is preferably 150°C or higher, more preferably 155°C or higher, and even more preferably 160°C or higher, and is preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower. When the stretching temperature is above the lower limit, the amine-based polymer is more likely to be unevenly distributed on the fiber surface, and therefore the nitrogen concentration ratio (surface / whole) and the nitrogen element concentration on the fiber surface are easily increased. When the stretching temperature is below the upper limit, the fiber sticking due to melting and the decrease in carbon dioxide absorption due to oxidative decomposition of the amine-based polymer are easily suppressed. In addition, the stretching time is preferably 5 seconds or more, more preferably 10 seconds or more, and preferably 60 seconds or less, and more preferably 40 seconds or less. When the stretching time is above the lower limit, the amine-based polymer is more likely to be unevenly distributed on the fiber surface, and therefore the nitrogen concentration ratio (surface / whole) and the nitrogen element concentration on the fiber surface are easily increased. When the stretching time is below the upper limit, the thermal decomposition of the amine-based polymer is easily suppressed. The stretching can be carried out in a conventional manner, for example in a hot air oven.
[0039] [Carbon dioxide absorption and desorption] The carbon dioxide absorbing fiber of the present invention can absorb carbon dioxide by contacting with carbon dioxide at a temperature lower than the carbon dioxide release temperature, preferably at least 20°C lower than the release temperature, and can desorb carbon dioxide by heating to a temperature equal to or higher than the carbon dioxide release temperature, preferably at least 50°C higher than the release temperature. The carbon dioxide absorbing fiber of the present invention can exhibit excellent carbon dioxide absorption even at the temperature, humidity, and amount of carbon dioxide in a living environment, and can be suitably used as a carbon dioxide absorbent in a living environment. In addition, since the carbon dioxide absorbing fiber is in a fibrous form, it has high strength and can be used in various applications, such as removing carbon dioxide in space suits and spacecraft. The application field is not particularly limited, and can be widely used, for example, in thermal power plants, ironworks, chemical plants, food, medicines, cosmetics, batteries, etc.
[0040] [Fiber assembly] The present invention includes a fiber assembly containing the carbon dioxide absorbing fiber. Specific examples of the fiber assembly include woven fabrics, knitted fabrics, nonwoven fabrics, felts, sponges, etc. Among these, the fiber assembly is preferably a nonwoven fabric from the viewpoints of good productivity and enabling uniform contact between solid and gas. EXAMPLES
[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.
[0042] <Viscosity average degree of polymerization> For PVA saponified to a degree of saponification of 99.5 mol% or more, the intrinsic viscosity [η] (liters / g) was measured in water at 30°C, and the viscosity average degree of polymerization (P) of the PVA in the examples and comparative examples was calculated according to the following formula. P = ([η] × 10 4 / 8.29) (1 / 0.62)
[0043] <Saponification degree> The saponification degree of PVA in the examples and comparative examples was measured in accordance with JIS-K6726.
[0044] <Number average molecular weight> The number average molecular weight of the amine-based polymers used in the examples and comparative examples was measured by gel permeation chromatography (GPC) using an HLC-8320GPCEcoSEC (manufactured by Tosoh Corporation) under the following conditions. Column: SHODEXOHpakSB-802.5HQ, SB-803HQ Column temperature: 40℃ Eluent: 0.5M acetic acid + 0.2M sodium nitrate aqueous solution / acetonitrile = 50 / 50 (volume ratio) Detector: RI Calibration curve: standard polyethylene glycol (Agilent Technologies, Inc.).
[0045] <Single yarn size> The single fiber fineness of the carbon dioxide absorbing fibers obtained in the Examples and Comparative Examples was calculated from the weight of a 20 m roll of the fiber.
[0046] <Carbon dioxide absorption> (Preparation of evaluation samples) The carbon dioxide absorbing fibers obtained in the examples and comparative examples were heat-treated in a hot air oven at 160°C for 3 minutes to remove the gas that had been absorbed beforehand, and then the carbon dioxide absorbing fibers were left to stand for 12 hours in an environment with an air temperature of 20°C, a relative humidity of 60%, and a carbon dioxide concentration of 400 ppm to absorb carbon dioxide. The amount of carbon dioxide absorbed by the carbon dioxide adsorption fibers left to stand for one week (168 hours) in the above environment was taken as the saturated absorption amount.
[0047] (Method for measuring carbon dioxide absorption) Using a gas adsorption measurement device "BELCAT II" (Microtrack BEL), the sample for evaluation prepared above was heated from room temperature to 200°C at 10°C / min, and the amount of released carbon dioxide was measured using BELMASS (Microtrack BEL). During the measurement, helium was flowed as a carrier gas at 100cc / min.
[0048] <Measurement of nitrogen element concentration on fiber surface> (XPS measurement) The nitrogen element concentration (mol%) on the fiber surface of the carbon dioxide absorbing fiber obtained in the examples and comparative examples was measured using a photoelectron spectrometer "JPS-9200" (manufactured by JEOL). MgKα was used as the excitation source. More specifically, the carbon dioxide absorbing fiber was thoroughly dried at room temperature under reduced pressure, and the carbon dioxide absorbing fiber was then washed with water at a concentration of 1×10 6 The measurement was performed under a vacuum of 1 Pa, with an analysis size of 1 mm and an incidence angle of 45°. The peak near 530 eV in the obtained spectrum was taken as the oxygen element, and the peak near 398 eV as the nitrogen element, and the element ratio of oxygen element to nitrogen element was calculated from the integral value and the relative sensitivity factor. Using the calculated element ratio, the following equation (1): Nitrogen concentration (mol%) = nitrogen amount (mol) / [nitrogen amount (mol) + oxygen amount (mol)] × 100 (1) From this, the nitrogen element concentration (mol %) on the surface of the carbon dioxide absorbing fiber was calculated.
[0049] <Measurement of nitrogen element concentration throughout the fiber> (Elemental analysis) Measurements were performed using an organic elemental analyzer "FLASH2000" (manufactured by Thermo Fishet) under CNHS analysis conditions: incinerator temperature 950°C, oven temperature 65°C, helium 140mL / min, oxygen 250mL flow. Sulfanilamide was used as the standard sample, tin foil was used as the sample container, the analytical material was 1.5mg, and the analysis time was 720 seconds. Using the obtained elemental ratio of oxygen element to nitrogen element, the nitrogen element concentration (mol%) of the entire carbon dioxide absorbing fiber was calculated according to the above formula (1).
[0050] <Measurement of the dynamic friction coefficient of carbon dioxide absorbing fiber> A load of 1 kg was applied to the carbon dioxide absorbing fibers obtained in the Examples and Comparative Examples, and the fibers were subjected to tension by pressing the measuring part of a dynamic friction coefficient measuring device (manufactured by Trinity Lab, product name: Trilab Handy Lab Tester) perpendicularly against the fibers and moving them 15 cm in the fiber axis direction to measure the dynamic friction coefficient. Approximately the same part was measured three times, and the average value was taken as the dynamic friction coefficient. The coefficient of kinetic friction can be calculated as follows: Coefficient of kinetic friction = kinetic friction force [N] / normal stress [N].
[0051] [Example 1] Polyvinyl alcohol (PVA, viscosity average polymerization degree 1700, saponification degree 99 mol%) hydrous chips were prepared and put into an extruder to dissolve the PVA. The dissolved PVA aqueous solution was mixed with an aqueous solution of polyethyleneimine ("Epomin SP-200", Nippon Shokubai Co., Ltd., number average molecular weight 10000, a polymer having a branched structure composed of primary amino groups, secondary amino groups, and tertiary amino groups) as an amine polymer, and the mass ratio of PVA to polyethyleneimine was set to 60 / 40. This stock solution was extruded into air at 100 ° C from a nozzle with 70 holes, dried, and wound up to obtain an undrawn fiber. The obtained undrawn fiber was drawn in a hot air furnace at 160 ° C at a draw ratio of 3 times and a draw time of 30 seconds to obtain a carbon dioxide absorbing fiber (fineness 35 dtex).
[0052] [Example 2] Carbon dioxide absorbing fibers (fineness: 14 dtex) were obtained in the same manner as in Example 1, except that the temperature of the hot air oven was 210° C. and the draw ratio was 5 times.
[0053] [Example 3] A carbon dioxide absorbing fiber (fineness: 10 dtex) was obtained in the same manner as in Example 1, except that the heat drawing ratio was changed to 7 times.
[0054] [Example 4] Carbon dioxide absorbing fibers (fineness: 12 dtex) were obtained in the same manner as in Example 1, except that the mass ratio of PVA to polyethyleneimine was 80 / 20 and the heat stretching ratio was 5 times.
[0055] [Example 5] Carbon dioxide absorbing fiber (fineness 14 dtex) was obtained in the same manner as in Example 1, except that the number average molecular weight of polyethyleneimine was 1200, the mass ratio of PVA to polyethyleneimine was 70 / 30, and the heat stretching ratio was 5 times.
[0056] [Comparative Example 1] A carbon dioxide absorbing fiber (fineness 70 dtex) was obtained in the same manner as in Example 1, except that the stretching treatment was not carried out.
[0057] [Comparative Example 2] A carbon dioxide absorbing fiber (fineness: 47 dtex) was obtained in the same manner as in Example 1, except that the stretching ratio was doubled.
[0058] For the carbon dioxide absorbing fibers obtained in Examples 1 to 5 and Comparative Examples 1 and 2, the nitrogen element concentration on the fiber surface, the nitrogen element concentration in the entire fiber, the nitrogen concentration ratio (surface / entire fiber) between the nitrogen element concentration on the fiber surface and the nitrogen element concentration in the entire fiber, the dynamic friction coefficient, the carbon dioxide (CO2) absorption amount after standing for 12 hours, and the saturated carbon dioxide (CO2) absorption amount were measured. The results are shown in Table 1.
[0059] [Reference example 1] A hydrous chip of polyvinyl alcohol (PVA, viscosity average polymerization degree 1700, saponification degree 99 mol%) was prepared and put into an extruder to dissolve the PVA. This stock solution was extruded into air at 100 ° C. from a nozzle with 70 holes, dried and wound up to obtain an unstretched fiber. The obtained unstretched fiber was stretched in a hot air furnace at 160 ° C. with a stretch ratio of 3 times and a stretching time of 30 seconds to obtain a polyvinyl alcohol fiber (fineness 35 dtex). This fiber was immersed in a 40 mass% aqueous solution of polyethyleneimine ("Epomin SP-200", Nippon Shokubai Co., Ltd., number average molecular weight 10000, polymer having a branched structure composed of primary amino groups, secondary amino groups and tertiary amino groups) as an amine-based polymer, and dried to obtain a carbon dioxide absorbing fiber. The mass ratio of polyvinyl alcohol / amine-based polymer after drying was 83 / 17. The dynamic friction coefficient of the carbon dioxide absorbing fiber was measured and found to be 1.1. In addition, the fibers generated fluff due to friction between the fibers when released. On the other hand, when the dynamic friction coefficient was 1.0 or less, fluff did not occur, and the fibers tended to have excellent quality, grade, fiber processability, and handleability.
[0060] [Table 1]
[0061] As shown in Table 1, it was confirmed that the carbon dioxide absorbing fibers obtained in Examples 1 to 5 had both a larger carbon dioxide absorption amount after standing for 12 hours and a larger saturated carbon dioxide absorption amount than those in Comparative Examples 1 and 2. Therefore, it was found that the carbon dioxide absorbing fibers of the present invention have excellent carbon dioxide absorption properties. In addition, the carbon dioxide absorbing fibers obtained in Examples 1 to 5 showed a low dynamic friction coefficient of 0.3, so no fluff was generated when released, and it was found to be excellent in fiber quality, grade, fiber processability, and handleability.
Claims
1. A carbon dioxide absorbing fiber containing polyvinyl alcohol and an amine-based polymer, The fiber is a composite fiber of polyvinyl alcohol and an amine-based polymer, A carbon dioxide absorbing fiber, wherein the nitrogen element concentration on the fiber surface is 1.40 times or more the nitrogen element concentration in the entire fiber.
2. The carbon dioxide absorbing fiber according to claim 1 , wherein the nitrogen element concentration on the fiber surface is 50 mol % or more.
3. The carbon dioxide absorbing fiber according to claim 1 or 2, wherein the content of the amine-based polymer is 5 to 50 mass % based on the mass of the carbon dioxide absorbing fiber.
4. The carbon dioxide absorbing fiber according to any one of claims 1 to 3, wherein the amine-based polymer is at least one selected from the group consisting of polyvinylamine, polyallylamine, polydiallylamine, polyalkyleneamine, polyethyleneimine, polydiallyl quaternary ammonium, and salts thereof.
5. The carbon dioxide absorbing fiber according to any one of claims 1 to 3, wherein the amine-based polymer is an amine-based polymer having a branched structure.
6. The carbon dioxide absorbing fiber according to any one of claims 1 to 5, wherein the number average molecular weight of the amine-based polymer is 500 to 50,000.
7. 7. A method for producing a carbon dioxide absorbing fiber according to claim 1, comprising: a step (1) of obtaining a spinning dope containing polyvinyl alcohol, an amine-based polymer, and a solvent; a step (2) of extruding the spinning dope into dry air and removing the solvent to form an undrawn fiber; and a step (3) of drawing the undrawn fiber to 2.5 times or more.
8. The method according to claim 7, wherein the stretching temperature in step (3) is 150 to 250°C.
9. A fiber assembly comprising the carbon dioxide absorbing fiber according to any one of claims 1 to 6.
10. The fiber assembly according to claim 9 , which is a nonwoven fabric.
Citation Information
Patent Citations
Copolymer composition, membranes, products, and methods thereof
JP2012519226A
Low swellable composition and manufacturing method therefor
JP2015120873A
Carbonic acid gas generating agent and nonaqueous electrolyte storage battery using the same
JP2019091577A
Carbon dioxide gas absorber, non-aqueous electrolyte storage battery containing same, and method for separating and recovering carbon dioxide gas
WO2019059368A1
